A further study on the wolf spider genus Hippasa Simon, 1885 from East Asia, with the description of a genus (Araneae: Lycosidae) - Wang, Lu-Yu; Li, Shuqiang; Marusik, Yuri M.; Zhang, Zhi-Sheng (Zootaxa, 2026)
Three new species of Hippasa are described from China and adjacent regions of Thailand and Vietnam: H. modog sp. nov. (♂♀, Xizang, China), H. pulmoniformis sp. nov. (♂♀, Guangxi, China, and Hải Phòng Province, Vietnam), and H. thailandica sp. nov. (♂♀, Suan Phueng, Thailand). A new genus, Pandacosa gen. nov., is established to accommodate Hippasa bifasciata Buchar, 1997 (previously known only from females in Bhutan). The male of Pandacosa bifasciata (Buchar, 1997) comb. nov. is described for the first time based on specimens from Yunnan, China. A distribution map for all treated species is provided.